PENGUATAN KARAKTER DI MADRASAH IBTIDAIYAH MELALUI POLA INTERAKSI KOLABORATIF - Lely Susiyani; Zaenu Zuhdi; A. Qomarudin (Al-Mudarris: Journal Of Education, 2025)
The development of children's character is basically greatly influenced by the parenting patterns of parents in everyday life in the family environment. So that a harmonious relationship in the family will greatly help teacher in the development of students/children's character at school. This study aims to examine in more detail the interaction patterns between teachers and students, parents and children, and teachers and parents at MI Miftahul Huda Ngenep Karangploso, Malang Regency. This study uses a qualitative approach with a case study research type. The results of this study indicate that 1) the way teachers and students communicate is carried out formally in classroom learning as a teacher and is carried out informally outside the classroom as a student's friend in order to communicate more closely; 2) the way parents and children communicate needs to be carried out intensively by giving advice, supervising activities, providing examples, providing motivation, and giving punishment; and 3) the way teachers communicate with parents is carried out by utilizing communication tools (handphone and whatsapp), visits to students' homes, and inviting parents to school at the beginning and end of the school year.